Eventization of religious heritage: case studies and practical considerations - Dowson, Ruth (The international journal of religious tourism and pilgrimage, 2020)
This paper examines the role that events can play in promoting religious tourism to a specific destination, in this case, Malta. It introduces practical examples that present creative ideas and demonstrate good practice that can be adopted and adapted for future planning in this context. The dramatic growth of events in our way of life, evidenced by their expansion as part of popular culture, in Europe as elsewhere, is mirrored by an increase in events across many different aspects of life. However, it should be remembered that events emerged from seasonal, life cycle, and celebratory religious origins. Throughout human history, societies have celebrated and mourned, coming together through the medium of events, and today millions of travellers visit destinations in order to participate in events that relate to religious practices, places, historical occurrences, and objects. Such tourists may visit from a religious motivation or be engaged from historical or other perspectives. Events may involve blurring the boundaries between the sacred and the non-sacred, and this is a key challenge for those involved in working with religious buildings, sites or artefacts. For example, what is an appropriate use of a religious site or building for events purposes? And what is inappropriate? How might activities and places be managed in order to respect the sacred elements, whilst providing practical facilities for visiting tourists? This paper details specific examples of the use of events to promote faith-based tourism in the UK, that can provide lessons, ideas and processes for designing and developing meaningful programmes and events to attract religious tourism visitors, in different environments.